Adding value to bank branch performance evaluation using cognitive maps and MCDA:a case study - Ferreira, Fernando A. F. (2020)
Bank branch performance evaluation is a difficult endeavour. Some of the main reasons for this difficulty are the complexity inherent in the variety of aspects considered in the evaluation, and the multiple and conflicting interests of the different stakeholders involved. In this paper, we show how cognitive mapping and measuring attractiveness by a categorical-based evaluation technique can be used to support the evaluation of bank branches through the development of multidimensional performance evaluation systems, and to deal explicitly with the trade-offs between the different dimensions of performance and interests of different stakeholders. A case study is discussed where these techniques are used in a constructive way, making the learning activity easier and introducing transparency in the decision-making process. The strengths and weaknesses of the integrated use of these two operational research techniques in this context are also discussed.